1995
DOI: 10.1074/jbc.270.8.3823
|View full text |Cite
|
Sign up to set email alerts
|

Veratryl Alcohol Oxidase from Pleurotus ostreatus Participates in Lignin Biodegradation and Prevents Polymerization of Laccase-oxidized Substrates

Abstract: Oxidative enzymes (laccases and peroxidases) isolated from the culture media of different fungi are involved in the basic mechanism of ligninolysis via radical intermediates. However, experiments aimed at reproducing natural biodegradation in vitro have been unsuccessful so far since the single biocatalysts alone are not able to solubilize lignins because of the simultaneous recondensation of these intermediates. FAD oxidases can prevent this side reaction in lignin depolymerization by reducing quinonoids and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(72 citation statements)
references
References 27 publications
4
66
0
2
Order By: Relevance
“…The two former conditions have been confirmed with acetosyringone, since voltametric and electron paramagnetic resonance studies have shown the true reversibility of the substrate reaction (19) and the long half-life of its phenoxy radical (35). In contrast, the -NO·-radical from HBT inactivates laccase, and due to its high reactivity, decays rapidly to benzotriazole and other inactive compounds (30).…”
Section: Discussionmentioning
confidence: 66%
“…The two former conditions have been confirmed with acetosyringone, since voltametric and electron paramagnetic resonance studies have shown the true reversibility of the substrate reaction (19) and the long half-life of its phenoxy radical (35). In contrast, the -NO·-radical from HBT inactivates laccase, and due to its high reactivity, decays rapidly to benzotriazole and other inactive compounds (30).…”
Section: Discussionmentioning
confidence: 66%
“…AAO is the main oxidases enzyme in B. adusta while laccase plays important role in L. squarrosulus. In some WRF both enzymes were observed during lignin degradation like P. ostreatus has shown that the concerted action of laccase and AAO, produces significant reduction in the molecular mass of soluble lignosulphonates [30]. AAO is H 2 O 2 -generating enzyme, in P. sajor-caju, P. ostreatus, P. eryngii, B. adusta and P. chrysosporium which has been purified and their properties characterized [31].…”
Section: Aaomentioning
confidence: 99%
“…This observation suggests that an extracellular dihydrolipoamide dehydrogenase might fulfill a similar role as an accessory enzyme for lignin degradation to aryl alcohol oxidase in Pleurotus ostreatus [20], whose catalytic mechanism has been investigated subsequently in more detail [37].…”
mentioning
confidence: 99%
“…Kirk & Farrell commented on this problem in their review of microbial lignin oxidation in 1987, noting that polymerisation of lignin is not prominent in vivo, therefore they suggested that phenoxy radical intermediates "are reduced back to the phenols by an undiscovered enzyme and/or mechanism that prevents polymerization" [19]. In basidiomycete Pleurotus ostreatus, a FAD-dependent aryl alcohol oxidase was shown in 1995 to reduce quinonoids and phenolic radicals, and to prevent polymerisation of laccase-generated phenolic compounds [20], but no further progress has been made to prevent lignin repolymerisation enzymatically, and no such enzyme has been identified in bacteria that can oxidise lignin.…”
Section: Introductionmentioning
confidence: 99%